Participation of ATP in Nonadrenergic, Noncholinergic Relaxation of Longitudinal Muscle of Wistar Rat Jejunum - Kaori Waseda; Tadayoshi Takeuchi; Mayuko Ohta; Yutaka Okishio; Akikazu Fujita; Fumiaki Hata; Tadashi Takewaki (Elsevier, 2005)
A role of ATP in nonadrenergic, noncholinergic (NANC) relaxations was examined in the Wistar rat jejunum. Electrical field stimulation (EFS) induced NANC relaxation of longitudinal muscle of the jejunal segments in a frequency-dependent manner. A purinoceptor antagonist, adenosine 3'-phosphate 5'-phosphosulfate (A3P5PS, 100 μM) inhibited the relaxation: relaxations induced by EFS at lower or higher frequencies were either completely or partially inhibited, respectively. After the jejunal segments had been desensitized to ATP, the relaxations were decreased to the same extent as those inhibited by A3P5PS. An inhibitor of small conductance Ca2+-activated K+ channels (SK channels), apamin (100 nM), completely inhibited EFS-induced relaxations. Treatment of the segments with an inhibitor of sarcoplasmic reticulum Ca2+-ATPase, thapsigargin (1 μM), significantly inhibited the relaxations. The exogenous ATP-induced relaxation of longitudinal muscle occurred with a concomitant decrease in intracellular Ca2+ levels. Apamin and thapsigargin abolished these ATP-induced responses. A3P5PS significantly inhibited the inhibitory junction potentials which were induced in the longitudinal muscle cells. In addition, apamin significantly inhibited the hyperpolarization that was induced by exogenous ATP in the cells. These findings in the Wistar rat jejunum suggest that ATP participates in the NANC relaxation via activation of SK channels induced by Ca2+ ions that are released from the thapsigargin-sensitive store site. Keywords:: ATP, rat jejunum, nonadrenergic, noncholinergic relaxation, SK channel, sarcoplasmic reticulum